The relationship between the Malaysian population, household income, inflation rate, and house prices / Adawiyatul Munirah Abdul Muttalib - Abdul Muttalib, Adawiyatul Munirah (2022)
The goal of this research is to see how different independent variables affect housing price in Malaysia by analysing the impact of the different variables on housing price in Malaysia. Real estate has become the safest but most expensive investment due to the continuous and consistent rise in real estate prices. Real estate is also considered to be the most profitable investment option. This research is done in hopes of finding the best variables that affect Malaysian housing prices. The variables to be observed in this study are the population growth, the average household income and the inflation rate. These variables will be tested to determine the relationship and significance against housing price. All variables including the dependent variable, housing price are all based in Malaysia. A twenty-year data collection period from 1999 to 2019 is used to determine the significance of the variables. The data is picked twice yearly with a six month difference in between totaling the data up to 40 observations. The data will be tested using Unit Root Test, Correlation Test or Covariance Analysis, Multiple Linear Regression Model, Coefficient of Determination and Adjusted R squared. Data will be collected in the form of secondary data from official government websites and trusted websites for reliability of outcome. The websites chosen are the Department of Statistics Malaysia and the official Bank Negara Malaysia website. This study can benefit many parties such as investors, who can use the outcomes of this study to predict the future price of property investments and gain more profits. This research can also benefit the government. By knowing specific variables that have been affecting house prices, the government can work n creating housing affordability to Malaysians of all income group. Literature reviews include many past studies on this similar topic and discuss how the outcome varies from each study. Research methodology of this study explains the methods used to process the outcome and how the methods and formulas are relevant and suitable with the study. Future research on this topic is very much welcome with adjustments on location, data collection, additional variables and other suitable adaptation.